The Role And Importance Of Gliah Neurotrophical Factors In Early Diagnosis Of Parkinson Disease - Abdukodirov Eldor Isroilovich; Matmurodov Rustambek Jumanazarovich; Khalimova Khanifa Muxsinovna; Muminov Bekzod Askarovhch; Naimov Olim Yunusovuch (Zien Journals, 2022)
The role and importance of glial neurotrophic factor in the early detection of Parkinson's disease has been assessed. Depending on the clinical forms and duration of the disease, the amount of glial neurotrophic factor in the blood serum of patients was analyzed.
Keywords: Parkinson's disease; GDNF; neuron; degeneration